Using Atrium as a Strategy for Bringing Daylight to the Central Space of the University Educational Buildings - Kassab, Ahmad said; Bsais, Mohammad Haitham; Issa, Yara (Latakia University Journal -Engineering Sciences Series, 2019)
The atrium has been implemented as an architectural feature used in deep, large buildings. It is mainly used to provide an indoor space that encourage people interaction and bring a good level of daylight into the central and adjacent dark spaces. Atrium is a space covered with multi-storey glass and it can be closed from one, two, three or four sides. It has been used by the Romans since ancient times in housing, and became a model for the design of public buildings with a large scale, in order to take the best advantage of the climatic conditions to fetch as much daylight as possible. As it is not usual now to develop a large building without having a form of atrium. The model of the atrium in the educational buildings has been adopted due to the high quality indoor environment that it provides for the students in terms of physical and psychological comfort. In addition to its aesthetic value, it has been considered as an architectural solution for many environmental problems related to lighting and ventilation faced by architects during the design process. However, the atrium did not get sufficient interest in most of universities buildings. As the bad designed atrium leads to uncomfortable temperature during the day. As well as the glare caused by allowing too much daylight. The research presents a series of studies and discusses a range of methods and solutions that can improve the design of atrium and its performance for daylight by evaluating the atrium and propose modifications that fit the building structure. This evaluation focuses on two main aspects of the building; atrium geometry and the wall reflectance values. يعبر الفناء المسقوف واحدا من الاستراتيجيات المتبعة في المباني ذات المساحات الكبيرة و يستخدم بشكل أساسي لتأمين بيئة داخلية تشجع على التفاعل الاجتماعي و تؤمن الضوء الطبيعي لكافة فراغات المبنى بما فيها الفراغ العام الوسطي و يعرف الفناء المسقوف (atrium ) بأنه فراغ مسقوف بالزجاج متعدد الطوابق و قد يكون مغلق من جهة واحدة أو أكثر أو من جميع الجهات، و قد استخدمه الرومان منذ القدم في السكن ثم اعتمد نموذجا لتصميم المباني العامة ذات المقياس الكبير نظرا لكفاءته العالية البيئية، إذ انه من غير المعتاد الآن تطوير مبنى كبير الحجم لا يحتوي على شكل من أشكال فراغ الفناء. و قد اتبع نموذج الفناء المسقوف في الفراغ العام الرئيسي في المباني التعليمية نظرا لما يوفره هذا الفراغ من بيئة داخلية عالية الجودة للطلاب من حيث الراحة الفيسولوجية و النفسية. حيث أنه بالإضافة إلى قيمته الجمالية، يعتبر أحد الحلول المعمارية لكثير من المشاكل البيئية المتعلقة بالإضاءة و التهوية و التشميس التي يواجهها المصممون المعماريون في عملية التصميم. و لم يلق هذا الفراغ الاهتمام الكافي في أغلب المباني الجامعية حيث يؤدي الفناء المصمم بشكل سيئ إلى درجات حرارة غير مريحة أثناء النهار، بالإضافة إلى الوهج الناتج عن السماح لضوء النهار بالنفاذ بشكل زائد. يقدم البحث مجموعة من الدراسات التي أجريت على الفناء المسقوف و يتطرق إلى مجموعة من الطرق و الحلول التي ممكن معها تحسين تصميمه و أداءه بالنسبة لضوء النهار من خلال تقييم الفناء واقتراح التعديلات التي تناسب تشكيل المبنى. يركز هذا التقييم على جانبين رئيسيين للمبنى، وهما التشكيل الهندسي للفناء وقيم انعكاس الجدار.